Elaborating Procedural Texts and Videos of Indonesian Culinary to Enhance Speaking Performances - Hasanah, Yuli Astuti (Institut Agama Islam Negeri Kudus, 2021)
The study described how the elaboration of creating procedural texts and videos of Indonesian culinary was used in selected EFL speaking classes in Kediri, Indonesia. The subjects of the research were the second-semester college students of IAIN Kediri. The researcher found that students had low performances in the speaking class. Classroom action research was applied to the study. The instruments used to collect the data were field notes, questionnaires, and interviews. Then, the data were analyzed descriptively. The result of the study identified that students increased collaboration of group working, confidence, learning motivation, and creativity. The study resulted those problems in speaking English could be solved through this technique. This study implies that the students improved their speaking performances by demonstrating procedural texts of making Indonesian culinary and recording them into videos that could be deliberately spread out through the YouTube website to share as valuable sources of knowledge and tutorials.